Political-organisational aspects for the prevention of genetic diseases - Orsini, Bruno (Medicina e Morale, 2024)
The explosive advances in medical genetics are, as is well known, very recent, but they already constitute major references in the preparation of the new models of health action postulated by the establishment of the national health service. They have made possible and at the same time necessitated extensive legislative and organisational design work for the prevention, diagnosis and treatment of genetic diseases. Translated with DeepL.com (free version)